“Estudio del liderazgo participativo y la comunicación interna de los colaboradores en las Cooperativas de Ahorro y Crédito Ltda., del cantón La Maná provincia de Cotopaxi, año 2022”. - Garcia Medina, Steven Joel (2022)
The purpose of this research is to carry out a study of participative leadership and internal communication of the collaborators in the 13 Cooperatives of Savings and Credit Ltda., from La Maná, which allows to clearly determine the climate and environment work, internal communication, teamwork, motivation and job satisfaction and quality service within the same as the work functions are developed; it is widely related to the administrative process such as planning, management and control to form whose purpose is to achieve the proposed objectives. In the field research it is diagnosed that data and information were obtained through the application of the surveys directed to the 13 agency chiefs or managers and to the 120 collaborators, whose results allowed us to know that there was a high level of ignorance of the participative leadership. The Cooperatives in which the research study was carried out are: COAC Futuro Lamanense, COAC Occidental, COAC 9 de Octubre, COAC Virgen del Cisne, COAC Cámara de comercio, COAC Innovación andina, COAC Sierra Centro, COAC Sumak Kawsay, COAC Andina, COAC Cacpeco, COAC Coorcotopaxi, COAC Finanzas Corporativas, COAC Vencedores Tungurahua. In the context of participatory leadership, the term participation can be defined as the influence that results from a person taking an active part in the decision making process and where knowledge, experiences and good practices are shared in the service of their work activities, thus developing new outstanding leaders rights, with transparency and recognition of all in their natural roles participate in within the financial institution. The present research proposal was given by an action plan on participatory leadership as an alternative to improve the work climate and performance of the functions of the collaborators to publicize in the savings and credit cooperatives Ltda., from La Maná.